Mechanisms of High Temperature Superconductivity : Proceedings of the 2nd NEC Symposium, Hakone, Japan, October 24-27, 1988 - Kamimura, Hiroshi (Springer series in materials science, 1989)
Since the discovery by Bednorz and Müller of Cu-O alloys displaying high temperature superconductivity, great energy has been put into research in this field. One of the most important and interesting issues, and the subject of this volume, is the clarification of the microscopic origin and mechanism of high temperature superconductivity. This book discusses the latest experimental results on magnetic, optical, electrical, thermal and mechanical properties of the Cu-O and Bi-O superconductors, as well as proposed theoretical models of the mechanisms. The participants in the symposium agreed that for the high Tc Cu-O superconductors electron correlation effects are of central importance. For the Bi-O superconductors the main topic was whether the mechanism of superconductivity is the same as that of high Tc Cu-O superconductors. What was and what was not resolved at the symposium is summarized at the end of the volume.